2003
DOI: 10.1007/bf03179875
|View full text |Cite
|
Sign up to set email alerts
|

Influencia del ayuno en el efecto del aceite de coco sobre la composición del plasma y de las lipoproteínas de pollo

Abstract: For a better understanding of the hyperlipidemic function of saturated fat, we have studied the effects of diet supplementation with 10-20% coconut oil on the chick plasma and lipoprotein composition under postprandial and starvation conditions. A significant hypercholesterolemia was found in chicks fed the standard diet after 12 h of food deprivation. In these conditions, LDL-cholesterol also increased, whereas triglyceride levels were reduced in HDL, VLDL and chylomicron fractions. Coconut oil induced a sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…A similar decrease in plasma TAG during starvation was also reported in some carnivorous fish ( 57 , 58 ) , but this decrease was associated with an increase in cholesterol. In humans and animal models, similar conflicting data regarding the effects of fasting on plasma TAG and cholesterol have also been found ( 17 21 ) . These inconsistencies may originate from sex, age, obesity, hyperlipidaemia, health state, medication, diets and/or physical activity during fasting ( 17 ) .…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…A similar decrease in plasma TAG during starvation was also reported in some carnivorous fish ( 57 , 58 ) , but this decrease was associated with an increase in cholesterol. In humans and animal models, similar conflicting data regarding the effects of fasting on plasma TAG and cholesterol have also been found ( 17 21 ) . These inconsistencies may originate from sex, age, obesity, hyperlipidaemia, health state, medication, diets and/or physical activity during fasting ( 17 ) .…”
Section: Discussionmentioning
confidence: 82%
“…The regulation of these pathways affects the lipid metabolism and was effectively demonstrated to modulate blood lipid composition in both animal models and humans ( 16 18 ) . The observations regarding blood lipid alteration during fasting are conflicting ( 17 21 ) , but hypolipidaemic effects have been reported ( 18 , 22 ) .…”
mentioning
confidence: 99%
“…ApoB‐48 is the main lipoprotein produced by the human intestine, and it generally disappears after an overnight fast (28). Previous animal studies have suggested that chylomicron levels remain unchanged, even during periods of starvation (29,30). The long‐term effect of PN on chylomicron formation in a child with an underlying intestinal motility disorder is unknown, and prolonged PN in the absence of enteral feedings could affect chylomicron levels.…”
Section: Discussionmentioning
confidence: 99%
“…This is an unnatural form of coconut oil that is purposely altered to make it completely devoid of any essential fatty acids. The conclusion that can be drawn from such animal research is that feeding hydrogenated coconut oil devoid of essential fatty acids enhances the formation of atherosclerosis markers [13]. However, coconut oil, unlike much of the soybean and corn oil consumed both here and abroad, is free of hydrogenated fat and hence transfatty acids.…”
Section: Coconut Fats and Lipidsmentioning
confidence: 99%